Knowledge Management as the Primary Driver of Innovation Capability and Entrepreneur Performance in Indonesian Batik SMEs - Irwan Sugiarto; Horas Djulius; Heru Setiawan (Global Research Collaboration, 2026)
This study examines the effects of Entrepreneurial Leadership, Intellectual Capital, and Knowledge Management on Innovation Capability and investigates the implications of Innovation Capability for Entrepreneur Performance among Indonesian batik Micro, Small, and Medium Enterprises (MSMEs). The study addresses inconsistencies in the literature regarding the relative importance of organizational capabilities in fostering innovation and business performance. A quantitative explanatory survey was conducted involving 166 batik MSME owners and managers in Garut Regency, Tasikmalaya Regency, and Tasikmalaya City, West Java, Indonesia. Data were collected through structured questionnaires and analyzed using path analysis with IBM SPSS Statistics 25. The results reveal that Entrepreneurial Leadership, Intellectual Capital, and Knowledge Management positively and significantly influence Innovation Capability. Among these variables, Knowledge Management emerged as the strongest predictor of Innovation Capability (β = 0.454), followed by Intellectual Capital (β = 0.346) and Entrepreneurial Leadership (β = 0.335). Furthermore, Innovation Capability demonstrated a strong positive effect on Entrepreneur Performance (β = 0.862). The model explained 72.2% of the variance in Innovation Capability and 74.3% of the variance in Entrepreneur Performance. This study extends the Resource-Based View, Knowledge-Based View, and Dynamic Capabilities Theory by identifying Knowledge Management as the dominant organizational capability driving innovation within knowledge-intensive cultural SMEs. The findings provide new insights into how organizational resources are transformed into innovation and business performance in traditional creative industries.